2017
DOI: 10.2147/jpr.s131479
|View full text |Cite
|
Sign up to set email alerts
|

The Central Sensitization Inventory validated and adapted for a Brazilian population: psychometric properties and its relationship with brain-derived neurotrophic factor

Abstract: ObjectivesThe primary aim was to assess the psychometric properties (including internal consistency, construct validity, reproducibility, and factor structure) of the Central Sensitization Inventory (CSI), adapted and validated for a Brazilian population (CSI-BP). Additionally, we evaluated the relationship between the CSI-BP and the serum brain-derived neurotrophic factor (BDNF) and determined if the symptoms elicited by the CSI-BP discriminate between subjects who do/do not respond to the conditioned pain mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
140
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(157 citation statements)
references
References 53 publications
8
140
2
7
Order By: Relevance
“…Previous studies have found satisfactory test‐retest reliability (intraclass correlation coefficient [ICC] = 0.88 to 0.97) and internal consistency (Cronbach’s alpha = 0.88 to 0.91) . Although the CSI does not actually measure CS, CSI scores have been found to be associated with subjective and objective CS‐related variables, including lower pain thresholds, wider distribution of pain, longer pain duration, levels of brain‐derived neurotrophic factor, and dysfunction of the descending pain‐modulatory system . Also, total CSI scores have been found to discriminate between subjects with presumably different levels of CS, including patients with chronic regional pain, widespread pain/FM, and controls .…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies have found satisfactory test‐retest reliability (intraclass correlation coefficient [ICC] = 0.88 to 0.97) and internal consistency (Cronbach’s alpha = 0.88 to 0.91) . Although the CSI does not actually measure CS, CSI scores have been found to be associated with subjective and objective CS‐related variables, including lower pain thresholds, wider distribution of pain, longer pain duration, levels of brain‐derived neurotrophic factor, and dysfunction of the descending pain‐modulatory system . Also, total CSI scores have been found to discriminate between subjects with presumably different levels of CS, including patients with chronic regional pain, widespread pain/FM, and controls .…”
Section: Introductionmentioning
confidence: 98%
“…20,21,25,26 Also, total CSI scores have been found to discriminate between subjects with presumably different levels of CS, including patients with chronic regional pain, widespread pain/FM, and controls. 16,20,21 In a recent systematic review, researchers concluded that the CSI generates reliable and valid data to quantify the severity of CS-related symptoms. 27 A CSI score > 40 has been recommended as a reasonable cutoff score for alerting clinicians that further assessment for CS symptomology is warranted.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher CSI scores have been associated with a wider body area distribution of self‐reported pain in a group of osteoarthritis patients scheduled to undergo primary total knee arthroplasty and increased widespread pain sensitivity in shoulder patients undergoing quantitative sensory testing . In addition, CSI scores have been found to correlate with other objective biological markers of CS, including brain gamma‐aminobutyric acid levels in migraine subjects and serum brain‐derived neurotrophic factor in fibromyalgia, myofascial pain, and osteoarthritis knee patients, compared to pain‐free control subjects …”
Section: Introductionmentioning
confidence: 99%